BMA for the BMA: Boosting Mobility Analysis for the Bangkok Metropolitan Administration via Automated Pedestrian Counting from CCTV - Kujareanpaisal, Poonnaphop; Mayhasap, Rujira; Tea-Makorn, Pin Pin; Jindahra, Pavitra; Starita, Stefano; Cooharojananone, Nagul; Atchariyachanvanich, Kanokwan (My University, 2024)
The objective of detecting and counting people using the CCTV camera on the footpath is to facilitate and reduce the time required to count the number of people traveling in pedestrian areas without having to actually visit the area. This paper uses the head detection technique to solve the problem of overlapping objects, YOLOv8n for detection and BoT-SORT for object tracking. A program was developed to assist the Bangkok Metropolitan Administration in counting the number of people within the region of interest and visualizing the statistics. Users can view statistics in the form of visual charts to compare the maximum number of people in each period by importing the video into the program. Users can also view historical statistics from previously imported videos. This program enables users to monitor pedestrian traffic in each area, providing valuable insights for urban planning decisions.
Keywords: BoT-SORT; CCTV; Computer Vision; Data Augmentation; Human Detection; Pedestrian Counting; YOLO